The Vulval Disease Quality of Life Index in women with vulval lichen sclerosus correlates with clinician and symptom scores. (14th November 2019) - Felmingham, Claire; Chan, Lydia; Doyle, Lex W; Veysey, Emma
Abstract: Background/Objectives: The Vulval disease Quality of Life Index (VQLI) is a new tool that assesses the burden of vulval disease on quality of life (QoL). Our objective was to assess the correlation between VQLI score and clinician‐rated severity scores, overall patient itch/discomfort, disease duration, sexual activity, and age, in vulval lichen sclerosus (VLS) at a vulval disorders clinic. Methods: A retrospective case note review, including consecutive women with VLS who attended the clinic between April and October 2018. Outcome measures include the VQLI score, clinician‐rated severity score, and patient symptom score. Results: A total of 109 women with VLS were included. On multivariable analysis, there was evidence of a positive relationship between VQLI scores and the total clinician‐rated score (mean increase in VQLI score per unit increase in clinician score 1.34, 95% confidence interval [CI] 0.31, 2.38; P = 0.01); the relationship was stronger for the cutaneous component. There was little evidence for relationships of the VQLI with the patient's age, sexual activity or time since onset of symptoms. There was strong evidence for a positive relationship between VQLI score and overall itch/discomfort score (mean increase 2.38, 95% CI 1.88, 2.88; P < 0.001). New and follow‐up data were obtained on sequential visits for 12 women, among whom the VQLI score dropped a mean −2.75 points between visits (95% CI −6.05, 0.55; P = 0.094). Conclusion: The clinician‐rated severity correlates with the impact of VLS on QoL. The VQLI captures information included in a patient itch/discomfort score, which can be easily incorporated into routine assessment.